Altered gut–liver axis and hepatic adiponectin expression in OSAS: novel mediators of liver injury in paediatric non-alcoholic fatty liver. Issue 8 (11th June 2015) - Nobili, Valerio; Alisi, Anna; Cutrera, Renato; Carpino, Guido; De Stefanis, Cristiano; D'Oria, Valentina; De Vito, Rita; Cucchiara, Salvatore; Gaudio, Eugenio; Musso, Giovanni
Abstract : Background: Mechanism(s) connecting obstructive sleep apnoea syndrome (OSAS) to liver injury in paediatric non-alcoholic fatty liver disease (NAFLD) are unknown. We hypothesised alterations in gut–liver axis and in the pool and phenotype of hepatic progenitor cells (HPCs) may be involved in OSAS-associated liver injury in NAFLD. Methods: Eighty biopsy-proven NAFLD children (age, mean±SD, 11.4±2.0 years, 56% males, body mass index z -score 1.95±0.57) underwent a clinical–biochemical assessment, with measurement of insulin sensitivity, plasma cytokines, lipopolysaccharide (LPS), an intestinal permeability test and a standard polysomnography. Hepatic toll-like receptor (TLR)-4 expression by liver-resident cells and overall number and expression of resistin and adiponectin by HPCs were assessed by immunofluorescence and immunohistochemistry. OSAS was defined by an apnoea/hypopnoea index ≥1. Results: OSAS was characterised by an increased intestinal permeability and endotoxemia, coupled with TLR-4 upregulation in hepatocytes, Kupffer and hepatic stellate cells (HSCs) and by an expansion of an adiponectin-deficient HPC pool, key features of steatohepatitis and fibrosis. The duration of haemoglobin desaturation (SaO2 <90%) independently predicted intestinal permeability (β: 0.396; p=0.026), plasma LPS (β: 0.358; p=0.008) and TLR-4 expression by hepatocytes (β: 0.332; p=0.009), Kupffer cells (β: 0.357; p=0.006) and HSCs (β:0.445; p=0.002). SaO2 <90% predicted also HPC number (β: 0.471; p=0.001) and impaired adiponectin expression by HPC pool (β: −0.532; p=0.0009). These relationships were observed in obese and non-obese children. Conclusions: In paediatric NAFLD, OSAS is associated with increased endotoxemia coupled with impaired gut barrier function, with increased TLR-4-mediated hepatic susceptibility to endotoxemia and with an expansion of an adiponectin-deficient HPC pool. These alterations may represent a novel pathogenic link and a potential therapeutic target for OSAS-associated liver injury in NAFLD.